A robust video watermarking scheme using sparse principal component analysis and wavelet transform. (2017) - Shankar, Thirunarayanan; Yamuna, Govindarajan
The extension of internet facility profoundly eases the dissemination of all digital data such as audio, images and videos to the general public. This paper proposes a blind scheme for digital video watermarking. In this paper, a discrete wavelet domain watermarking is adopted for hiding a large amount of data with high security, good invisibility and no loss to the secret message. At first, dual tree complex wavelet transform (DTCWT) is applied on each frame decomposing it into a number of sub-bands. Then, holo entropy of each sub-band is calculated and the maximum entropy blocks are selected. The selected blocks are transformed using sparse principal component analysis (SPCA). The maximum coefficient of the SPCA blocks of each sub-band is quantised using quantisation index modulation (QIM). The proposed video watermarking scheme is analysed through various constraints such as the normalised correlation (NC) and the peak signal to noise ratio (PSNR).